Under the Cover : The Creation, Production, and Reception of a Novel - Childress, Clayton (Book collections on Project MUSE., 2019)
Under the Coverfollows the life trajectory of a single work of fiction from its initial inspiration to its reception by reviewers and readers. The subject isJarrettsville, a historical novel by Cornelia Nixon, which was published in 2009 and based on an actual murder committed by an ancestor of Nixon's in the postbellum South.Clayton Childress takes you behind the scenes to examine howJarrettsvillewas shepherded across three interdependent fields-authoring, publishing, and reading-and how it was transformed by its journey. Along the way, he covers all aspects of the life of a book, including the author's creative process, the role of the literary agent, how editors decide which books to acquire, how publishers build lists and distinguish themselves from other publishers, how they sell a book to stores and publicize it, and how authors choose their next projects. Childress looks at how books get selected for the front tables in bookstores, why reviewers and readers can draw such different meanings from the same novel, and how book groups across the country make sense of a novel and what it means to them.Drawing on original survey data, in-depth interviews, and groundbreaking ethnographic fieldwork,Under the Coverreveals how decisions are made, inequalities are reproduced, and novels are built to travel in the creation, production, and consumption of culture.